Challenges and Solutions in Implementing the Nazhāriyyah Al Wahdah System in Arabic Language Learning: A Case Study from India - K M A Ahamed Zubair (Indonesian Journal of Innovative Teaching and Learning, 2026)
Background: Arabic language instruction has increasingly adopted the integrated system known as Nazhāriyyah Al Wahdah, which conceptualises language as a unified communicative whole rather than separate linguistic components; however, its implementation in diverse higher education contexts remains insufficiently examined. Objective: This study aims to analyse the challenges and identify strategic solutions for applying Nazhāriyyah Al Wahdah at the undergraduate level in the Department of Arabic at The New College, Chennai, India. Method: Using a qualitative case study design, data were collected through in-depth interviews, participatory observation, and document analysis, and were analysed using an interactive analytical model. Result; The findings reveal that limited instructional time and the absence of a language laboratory significantly hinder effective skill integration, resulting in uneven student proficiency. While grammar (tarkib) and dialogue (hiwar) demonstrate relatively stronger engagement, listening (istima’), vocabulary application (mufradat), translation, and extended writing (kitabah) remain underdeveloped. Conclusion: Ssuccessful implementation requires institutional alignment, professional teacher competence, and the establishment of an immersive Arabic language environment (bi’ah lughawiyah). Contribution: The research contributes by clarifying the gap between structural and functional integration and by extending the discourse on integrated Arabic pedagogy to a non-Indonesian context.